1976
DOI: 10.1002/jcp.1040890452
|View full text |Cite
|
Sign up to set email alerts
|

The function and activity of certain membrane enzymes when localized on – and off – the membrane

Abstract: A group of enzymes known to be involved in group translocation-type transport mechanisms for the uptake of a variety of nucleotide precursors are enzymatically active both in their natural membrane milieu and in aqueous solution. The activity in aqueous solution markedly differ, however, from the enzymatic activity when the enzyme is membrane localized. The adenine phosphoribosyltransferase (PRT) of E. coli (Hochstadt-Ozer and Stadtman, 71a) is capable of carrying out an exchange reaction between the base moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
2

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
3
15
2
Order By: Relevance
“…This holds especially for enyzmes. When they are bound to a lipid membrane, many enzymes change their properties and temperature dependencies 2 . In the 1970s, many studies have found deviations from a pure Arrhenius-behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This holds especially for enyzmes. When they are bound to a lipid membrane, many enzymes change their properties and temperature dependencies 2 . In the 1970s, many studies have found deviations from a pure Arrhenius-behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphoribosylation process, with the high-energy metabolite phosphoribosylpyrophosphate, may simultaneously provide the driving force for the active transport of Hyp and Gua (by group translocation) (13). We have not examined this apparently controversial proposal (15,20), but we have found biphasic Michaelis-Menten plots that suggest the existence of an additional low-affinity transport mechanism for Hyp and Gua (but not for the nucleosides).…”
Section: Discussionmentioning
confidence: 90%
“…The uptake, which was linear for at least 5 min in all cases, is expressed as nanomoles x (OD6oo x minutes)-'; 1 OD6w unit is the amount of cells that gives an OD6w of 1 if the cells are suspended in 1 ml (this corresponds to about 0.5 mg [dry weight] of cells). Except where otherwise stated, the labeled compounds were used at the following concentrations: [2-`4C]Ura, 10 ,uM, 0.1 ,uCi/ml; [8-14CJAde, 10 ,uM, 0.1 ,uCi/ml; [8-14C]Ado, 40 FLM, 0.5 ,Ci/mn; [8-14C]Gua, 20 ,uM, 0.1 ,Ci/ml; [8,5'-3H]Guo, 15 ,uM, 0.5 uCi/ml; [5,6_3H]Uri, 25 ,uM, 0.5 ,Ci/ml; [5-3Hlcytidine, 15 ,uM, 0.5 ,uCi/ml; 1-0-methyl-(a-D-[U-14C]gluco)pyranoside, 50 ,uM, 0.15 ,Ci/ml; or [3-4C]a-aminoisobutyric acid, 100 ,M, 0.1 ,uCi/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The resultant inosine is metabolized by a purine nucleoside phosphorylase activity, which may or may not be the same as that used in the first mechanism which resulted in extravesicular hypoxanthine, leading to hypoxanthine and additional ribose-l-P. The initial I^evious studies from this laboratory have shown that, when inosine interacts with isolated plasma membrane vesicles from cultured mouse fibroblast cells grown to high cell density, the predominant intravesicular transport product is ribose-l-P1 (Li and Hochstadt, 1976a,b;Hochstadt and Quinlan, 1976). The mechanism involves membrane-localized purine nucleoside phosphorylase acting in a group translocation reaction during which hypoxanthine is released on the exterior membrane surface while the ribose moiety is phosphorylated in the process of being transported across the membrane.In contrast, in polyoma transformed baby hamster kidney (BHK) cells there exist two mechanisms of inosine handling: one, similar to that we have described for the mouse fibroblast cells, in which group translocation occurs and depends on a transmembranal purine nucleoside phosphorylase and for which internal inosine is not a substrate (Hochstadt and Quinlan, 1976;Li and Hochstadt, 1976b) and a second mechanism which involves the uptake of intact inosine.…”
mentioning
confidence: 99%
“…The resultant inosine is metabolized by a purine nucleoside phosphorylase activity, which may or may not be the same as that used in the first mechanism which resulted in extravesicular hypoxanthine, leading to hypoxanthine and additional ribose-l-P. The initial I^evious studies from this laboratory have shown that, when inosine interacts with isolated plasma membrane vesicles from cultured mouse fibroblast cells grown to high cell density, the predominant intravesicular transport product is ribose-l-P1 (Li and Hochstadt, 1976a,b;Hochstadt and Quinlan, 1976). The mechanism involves membrane-localized purine nucleoside phosphorylase acting in a group translocation reaction during which hypoxanthine is released on the exterior membrane surface while the ribose moiety is phosphorylated in the process of being transported across the membrane.…”
mentioning
confidence: 99%